Thomas F. X. Noble, images, iconoclasm, and the carolingians, (The Middle Ages series), University of Pennsylvania Press, Philadelphia, 2009; 488 p., ISBN 978-0-8122-4141-9 - Peretó Rivas, Rubén (2011)
Fil: Peretó Rivas, Rubén.